2019
DOI: 10.1080/10919392.2019.1552749
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion of e-participation in public administrations: A systematic literature review

Abstract: Research on e-participation has grown significantly in the last years. This review focuses on public administrations, which are central actors in the solicitation and organization of e-participation and in the process of diffusion of more democratic decision-making in government contexts. However, research indicates that public administrations often struggle with technological and organizational changes, which suggests that e-participation initiatives may fail due to barriers within public administrations. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 137 publications
(76 reference statements)
0
39
0
2
Order By: Relevance
“…For instance, studies have shown the importance of agency leadership for the adoption of e-participation (e.g., Saebø et al, 2011). Studies also show that the prevailing norms of culture at the organization level play a role in how e-participation is implemented (Steinbach et al, 2019). The degree of openness among staff in the organization to the idea of public participation is a key parameter, as is the balance of views on whether e-participation should primarily be geared to improving institutional performance (for instance, making regulation or services better) or should serve broader democratic goals (e.g., educating the public and increasing civic engagement).…”
Section: Iv10 Understanding Values In Public Administrationmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, studies have shown the importance of agency leadership for the adoption of e-participation (e.g., Saebø et al, 2011). Studies also show that the prevailing norms of culture at the organization level play a role in how e-participation is implemented (Steinbach et al, 2019). The degree of openness among staff in the organization to the idea of public participation is a key parameter, as is the balance of views on whether e-participation should primarily be geared to improving institutional performance (for instance, making regulation or services better) or should serve broader democratic goals (e.g., educating the public and increasing civic engagement).…”
Section: Iv10 Understanding Values In Public Administrationmentioning
confidence: 99%
“…Activities that are often found in support of e-participation include: advertising the initiatives and having outreach plans (both offline and online); alternating electronic and physical meetings; providing educational material on the issues being discussed; and making linkages with other programmes or initiatives. This aspect is closely linked with the institutionalization of e-participation initiatives within organizational processes, a key factor of success (Steinbach et al, 2019).…”
Section: Iii2 Combining Online and Offline Activities In Support Of mentioning
confidence: 99%
See 3 more Smart Citations